Genetic Association of a Gain-of-Function IFNGR1 Polymorphism and the Intergenic Region LNCAROD/DKK1 With Behcet's Disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (WILEY, 2021)
Objective Behcet's disease is a complex systemic inflammatory vasculitis of incompletely understood etiology. This study was undertaken to investigate genetic associations with Behcet's disease in a diverse multiethnic population. Methods A total of 9,444 patients and controls from 7 different populations were included in this study. Genotyping was performed using an Infinium ImmunoArray-24 v.1.0 or v.2.0 BeadChip. Analysis of expression data from stimulated monocytes, and epigenetic and chromatin interaction analyses were performed. Results We identified 2 novel genetic susceptibility loci for Behcet's disease, including a risk locus in IFNGR1 (rs4896243) (odds ratio [OR] 1.25; P = 2.42 x 10(-9)) and within the intergenic region LNCAROD/DKK1 (rs1660760) (OR 0.78; P = 2.75 x 10(-8)). The risk variants in IFNGR1 significantly increased IFNGR1 messenger RNA expression in lipopolysaccharide-stimulated monocytes. In addition, our results replicated the association (P < 5 x 10(-8)) of 6 previously identified susceptibility loci in Behcet's disease: IL10, IL23R, IL12A-AS1, CCR3, ADO, and LACC1, reinforcing the notion that these loci are strong genetic factors in Behcet's disease shared across ancestries. We also identified >30 genetic susceptibility loci with a suggestive level of association (P < 5 x 10(-5)), which will require replication. Finally, functional annotation of genetic susceptibility loci in Behcet's disease revealed their possible regulatory roles and suggested potential causal genes and molecular mechanisms that could be further investigated. Conclusion We performed the largest genetic association study in Behcet's disease to date. Our findings reveal novel putative functional variants associated with the disease and replicate and extend the genetic associations in other loci across multiple ancestries.
Keywords: GENOME-WIDE ASSOCIATION; MHC CLASS-I; INTERFERON-GAMMA; SUSCEPTIBILITY LOCI; VARIANTS; IDENTIFICATION; IL23R-IL12RB2; COMPONENTS; BINDING; STATES